Adoption of Eco and Circular Economy-Innovation in Italy: exploring different firm profiles - Massimiliano Mazzanti; Francesco Nicolli; Stefano Pareglio; Marco Quatrosi (Fondazione Eni Enrico Mattei (FEEM), 2022)
Applying clustering techniques, this paper identifies homogeneous groups of enterprises within the heterogeneous landscape of the italian manufacturing tissue. The algorithm will be fed with data from a survey on a cross-section of SMEs in 2019. The set of questions span from economic and financial performances to innovation adoption (product, process, organization), to circular economy implementation and environmental protection. Clustering has been chosen to identify groups of firms with respect to multiple and diverse characteristics without any preexisting hypothesis on a possible relationship among the variables. Results will group profiles of enterprises considering the information on multi-dimensional aspects of a firm. Indeed, the overarching aim of this work is to single out common characteristics among the diverse landscape of enterprises within the manufacturing sector. This will in turn support (local and national) policy makers in better designing and targeting an appropriate set of policy instruments with respect to the relevant areas (i.e., circular economy, environmental protection, eco-innovation) of the ecological/sustainability transition. If the one-size-fits-all has not been proved a viable approach in policy making, a more targeted intervention at policy level tackling the consistent heterogeneity of the manufacturing tissue might improve the effectiveness of (sectorial) policies.
Keywords: O30; O44; O55; 330; Circular Economy; Sustainable production; Environmental Innovation; Cluster analysis; Firm profile